UNPLANNED PREGNANCY IN WOMEN THAT PARTICIPATED IN A GROUP OF FAMILY PLANNING (Fiep Bulletin - online, 2011)
The development of this study came after realized that the pregnancy attended by the Family Planning Program, still were pregnant and had not planned their children. OBJECTIVE: To understand the causes and feelings related to unplanned pregnancy in women that participated in a family planning group. METHODS: Exploratory and descriptive research field with quantitative and qualitative approach. Developed in a Family Health Unit - USF in the city of Sousa-PB. The population was consisted by women who participate in the family planning that was consisted of 25 women who became pregnant without planned the pregnancy. To collect of data we used a semi-structured questionnaire with 14 objective questions and four subjective. The Quantitative data were analyzed like as to constitute a database, which were statistically analyzed using SPSS software, version 14.0. The subjective questions were qualitatively analyzed using the Analysis of Collective Subject Discourse (CSD), proposed by Lefèvre and Lefèvre (2005). RESULTS: The distribution of women by the age ranged from 13 to 35 years, that 70% of pregnant women were aged 20 years old. All lived in a stable status, 70% of the sample had only completed elementary school and 30% completed, 80% from the interviewed considered themselves Catholic and the others don´t reported. Regarding occupational status, 10% were working as domestic unregistered, and 70% was unemployed. The main causes of unplanned pregnancy greatly reside in the use inconsistent / inadequate from contraceptive methods by various reasons such as lack of knowledge or incorrect knowledge about their used, and the unavailability of contraceptives at the family health unit. CONCLUSION: It was felt that awareness about family planning is limited primarily to contraception and do not include the freedom to choose the method so as not reaching the goal of the Family Planning Program.
Keywords: contraception; family planning; adolescent